Discovery of novel benzylquinazoline molecules as p97/VCP inhibitors - Zhang, Xiaoyi; Jiang, Lingna; Li, Yixin; Feng, Qiqi; Sun, Xiulin; Wang, Yaonan; Zhao, Ming (Frontiers in Pharmacology, 2023)
Protein p97 is an extensively investigated AAA ATPase with various cellular activities, including cell cycle control, ubiquitin-proteasome system, autophagy, and NF-κB activation. In this study, we designed and synthesized eight novel DBeQ analogs as potential p97 inhibitors. In p97 ATPase inhibition assay, compounds 6 and 7 showed higher potency than known p97 inhibitors, DBeQ and CB-5083. Compounds 4-6 dramatically induced G0/G1 phase arrest in the HCT116 cells, and 7 arrested the cells in both G0/G1 and S phases. Western blots showed elevated levels of SQSTM/p62, ATF-4, and NF-κB in HCT116 cells with the treatment of compounds 4-7, confirming their role in inhibiting the p97 signaling pathway in cells. In addition, the IC50 of compounds 4-6 against HCT116, RPMI8226, and s180 proliferation were 0.24-6.9 µM with comparable potency as DBeQ. However, compounds 4-6 displayed low toxicity against normal human colon cell line. Thus, compounds 6 and 7 were proved to be potential p97 inhibitors with less cytotoxicity. In vivo studies using the s180 xenograft model demonstrate that compound 6 inhibited tumor growth, led to a significant reduction of p97 concentration in the serum and tumor, indicated non-toxicity on the body weight and organ-to-brain weight ratios except of spleen at the dose of 90 μmol/kg/day for 10 days. Furthermore, the present study indicated that compounds 6 may not induce s180 mice myelosuppression often observed in the p97 inhibitors. In conclusion, compound 6 displayed high binding affinity to p97, great p97 ATPase inhibition, selective cytotoxicity, remarkable antitumor effect, and upregulated safety, which improved the clinical potential of p97 inhibitors.